Changes of Wilkins Ice Shelf over the past 15 years and inferences on its stability - Braun, Matthias; Humbert, Angelika; Moll, Albert (Cryosphere, 2009)
The Wilkins Ice Shelf is situated on the Antarctic Peninsula, a region where seven ice shelves disintegrated or retreated between 1995 and 2002. This study combines various remote sensing datasets from Wilkins Ice Shelf, with the aim of detecting its present and recent dynamics as well as recent changes. The survey includes structural mapping, ERS-1/2 SAR interferometry and analysis of ICESat GLAS ice surface elevation data. Ice front retreat rates from 1986 to 2008 showed several distinct break-up events, including one in February 2008, when 40% of a part of the ice shelf that connected two islands broke off. Surface elevations have been used to study tidal effects, crack formation and to estimate the ice thickness over the floating area. The derived interferometric velocities cover the south-eastern part of the ice shelf as well as major tributaries and reveal maximum inflow speeds of up to 330 m a -1. We show that drainage of melt ponds into crevasses were of no relevance for the break-up at Wilkins Ice Shelf. Buoyancy forces caused rift formation before the break-up in February 2008. Additionally, the evolution of failure zones of the order of tenths of kilometres in length in pre-conditioned locations at ice rises is shown. Investigation of the current (February 2009) situation shows that about 3100 km 2 at the Northern Wilkins Ice Shelf are endangered, however, there is no visible signature that the remaining 8000 km 2 are at risk. © 2009 Author(s).
UnivIS-Import:2015-04-20:Pub.2009.nat.dgeo.IG.pgfgis.change